Fault tolerant predictive control design for reliable microgrid energy management under uncertainties. (November 2015) - Prodan, Ionela; Zio, Enrico; Stoican, Florin
Abstract: This paper presents an extension of a MPC (Model Predictive Control) approach for microgrid energy management which takes into account electricity costs, power consumption, generation profiles, power and energy constraints as well as uncertainty due to variations in the environment. The approach is based on a coherent framework of control tools, like mixed-integer programming and soft constrained MPC, for describing the microgrid components dynamics and the overall system control architecture. Fault tolerant strategies are inserted in order to ensure the proper amount of energy in the storage devices such that (together with the utility grid) the essential consumer demand is always covered. Simulation results on a particular microgrid architecture validate the proposed approach. Highlights: Model Predictive Control and fault tolerant design for reliable microgrid energy management. Mixed-integer Linear Programming for storage scheduling. Essential and non-essential user demand satisfaction via soft constraints implementation. Constraint and control reconfiguration for fault mitigation.